3642 Down the Rabbit Hole: Case Reports of a Hallucinogen-induced Disorder of Neuroperception - McConnell, Anneliese; He, Wei; McConnell, Harry; Sprendei, Sandro; Sowman, Paul (BMJ Publishing Group Ltd, 2025)
Background/Objectives We present case histories of severe adverse effects associated with Hallucinogen Persisting Perception Disorder (HPPD), a disorder of neuroperception involving visual and other senses that is due to the treatment of various neuropsychiatric disorders with hallucinogens. This includes the case of a young woman who developed visual hallucinations of distorted shapes and colours after participating in a clinical trial of psilocybin for treatment-resistant depression. She continued to have ongoing perceptual abnormalities, and other neuropsychiatric phenomena with severe effects on her quality of life. Objective To discuss the ramifications of HPPD stemming from treatment with psychedelics for neuropsychiatric disorders and the importance this holds for clinical practice and research trials. Methods We present case histories of people with HPPD, with a focus on a case occurring during a research trial as well as a systematic review of HPPD occurring with therapeutic use of hallucinogens. Results HPPD affects approximately 1 in 25 people taking psychedelics whether recreationally or therapeutically. HPPD occurs irrespective of dosing or frequency of use and may occur in those who have microdosed. HPPD may have serious long-term consequences often associated with other perceptual and neuropsychiatric symptoms. Conclusion HPPD is a potentially devastating adverse effect of hallucinogens irrespective whether the use occurs recreationally, therapeutically or even in a controlled trial. It is important that HPPD be screened for and that informed consent is obtained from patients with reference to this adverse effect. Patient education prior to being offered therapeutic hallucinogens is essential for clinical and research practice.